Development of Arabic Language Curriculum at MAN Pacitan - Biqi Asshafah Zain (Penerbit Hellow Pustaka, 2026)
This study aims to discuss the characteristics of the Arabic curriculum at MAN Pacitan, the policies taken by MAN Pacitan in developing the Arabic curriculum, and the supporting and inhibiting factors in the development of the Arabic curriculum at MAN Pacitan and their solutions. This study uses a qualitative approach with a descriptive type, which aims to describe in depth and factually the implementation, obstacles, and solutions in the development of the Arabic curriculum at MAN Pacitan. Data collection was carried out through participatory observation, in-depth interviews, and documentation, with data analysis using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of this study indicate that the characteristics of the development of the Arabic curriculum at MAN Pacitan are Perennial-Essentialist Contextual Falsificative. MAN Pacitan provides flexibility to teachers in developing five curriculum components, supported by teacher training programs at the beginning of each semester and Firqatul Lughah extracurricular activities to improve student competencies. Supporting factors for curriculum development include good coordination between teachers, between teachers and school management, and community participation. Meanwhile, curriculum development faces various obstacles such as diverse student backgrounds, low internal motivation, negative perceptions of Arabic, lack of teacher participation in curriculum development, minimal community attention, and limited funding. Solutions include the use of At-Tashil textbooks, the formation of small discussion groups, the creation of Arabic vocabulary songs, the use of manual and digital dictionaries, regular teacher training, improved internal coordination, and the optimization of available resources and facilities.